Analisis Semiotika pada Cover Majalah Tempo Edisi 4 - 11 Juni 2018 - Nugroho Abraham Akbar (Jurnal Spektrum Komunikasi, 2018)
Layout placement magazine is the most attention, because magazines have more space for pictures and photos. So images or photos can represent the contents of news or information delivered. A photo in a magazine must have information to clarify the photo. In addition to content with an attractive layout, something that draws attention to the magazine is the cover. In this study, the authors used a qualitative research method with a semiotic approach method. Semiotics Charles Sanders Pierce, the signs in the picture can be seen from the types of signs that are classified in semiotics. Among them: icons, indexes and symbols. The result is that every element contained in the cover produces meaning that can be understood by anyone who reads it. Because each photo is illustrated with a picture of each character in it. As for the other signs that are in it are also discussed based on the meaning and function of its use.